2003
DOI: 10.1084/jem.20031598
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Viremia Prevents the Establishment of Interleukin 2–producing HIV-specific Memory CD4+ T Cells Endowed with Proliferative Capacity

Abstract: CD4+ T cell responses are associated with disease control in chronic viral infections. We analyzed human immunodeficiency virus (HIV)-specific responses in ten aviremic and eight viremic patients treated during primary HIV-1 infection and for up to 6 yr thereafter. Using a highly sensitive 5-(and-6)-carboxyfluorescein diacetate-succinimidyl ester–based proliferation assay, we observed that proliferative Gag and Nef peptide-specific CD4+ T cell responses were 30-fold higher in the aviremic patients. Two subsets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
374
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(410 citation statements)
references
References 51 publications
(73 reference statements)
32
374
1
2
Order By: Relevance
“…20,29,42 HIV-1 viremia, in particular, impedes the establishment of IL-2-producing HIV-1-specific memory CD4 T cells endowed with proliferative capacity. 43 Several lines of evidence indicate that the proliferative capacity is maintained in primary and nonprogressive HIV-1 infection and impaired in chronic progressive infection. 16,20,44 Whether the proliferative impairment is reversible by endogenous or exogenous To account for multiple comparisons, differences between the functional groups were assessed by nonparametric KruskalWallis test for four-way comparison, followed by a pairwise Mann-Whitney test.…”
Section: Discussionmentioning
confidence: 99%
“…20,29,42 HIV-1 viremia, in particular, impedes the establishment of IL-2-producing HIV-1-specific memory CD4 T cells endowed with proliferative capacity. 43 Several lines of evidence indicate that the proliferative capacity is maintained in primary and nonprogressive HIV-1 infection and impaired in chronic progressive infection. 16,20,44 Whether the proliferative impairment is reversible by endogenous or exogenous To account for multiple comparisons, differences between the functional groups were assessed by nonparametric KruskalWallis test for four-way comparison, followed by a pairwise Mann-Whitney test.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indeed shown that the proliferation capacity of virus-specific CD4 and CD8 T cells is dependent upon the presence of IL-2-producing cells and that the presence of virus-specific proliferating cells is associated with control of virus replication [22,24,25]. Both CD4 1 ( Fig.…”
Section: Impaired Proliferation Of Hcv-specific T Cells In Patients Wmentioning
confidence: 90%
“…In particular, it has been shown that immune responses associated with effective virus clearance or control (low to undetectable viral load) were predominantly composed of polyfunctional CD4 1 and CD8 1 T cells. Polyfunctionality has been defined by the ability of both CD4 1 and CD8 1 T cells to produce cytokines such as IL-2 and IFN-g and to proliferate [22][23][24][25]. Other cytokines such as MIP-1b and TNF-a and functions such as degranulation activity and perforin expression are instrumental to better characterize the functional profile of T cells but do not discriminate between polyfunctional and ''only effector'' T-cell responses.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that HIV-specific CD4 ϩ T cells are skewed by viral replication toward an effector memory T (T Em ) cell 3 phenotype as identified by the loss of CCR7 and the acquisition of CD57 (1,2). HIV-specific CD4 ϩ T Em cells from subjects with chronic HIV infection proliferate poorly and lack the ability to secrete IL-2 (2-4).…”
Section: T Cell Dysfunction In Chronic Hiv Infection Is Closelymentioning
confidence: 99%